2020
DOI: 10.3390/jpm10020020
|View full text |Cite
|
Sign up to set email alerts
|

Flotillin: A Promising Biomarker for Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is characterized by the accumulation of beta amyloid (Aβ) in extracellular senile plaques and intracellular neurofibrillary tangles (NFTs) mainly consisting of tau protein. Although the exact etiology of the disease remains elusive, accumulating evidence highlights the key role of lipid rafts, as well as the endocytic pathways in amyloidogenic amyloid precursor protein (APP) processing and AD pathogenesis. The combination of reduced Aβ42 levels and increased phosphorylated tau protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 70 publications
(126 reference statements)
1
21
0
Order By: Relevance
“… Highly schematized representation of ( A ) the release of exosomes (EXs) and ( B ) the release and uptake of extracellular microvesicles (EMVs) in neural cells of the human central nervous system (CNS); both types of vesicular transport systems have been observed to operate in the brain between astroglial cells and neurons; ( A ) exosomes—when mature intracellular endosomes (also known as multi-vesicular bodies) containing intraluminal vesicles (ILVs; black outlined green spheres) fuse with the plasma membrane and empty their plasma membrane-encapsulated cargo, ILVs are released and, from being extracellular, they become exosomes (EX); these 30–100 nm diameter spheres contain various mixtures of proteins, lipids, proteolipids, cytokines, chemokines, microRNAs (miRNA), messenger RNAs (mRNA) and end-stage neurotoxic metabolic products, including 42 amino acid amyloid-beta (Aβ42) peptides, tau proteins and/or the lipid raft associated flotillin (Angelopoulou et al 2020 [ 29 ]; Hornung et al, 2020 [ 30 ]); EXs appear to play a central role in the spread of Aβ42 pathology and amyloidogenesis (Mathews and Levy 2019 [ 15 ]; Arbo et al, 2020 [ 6 ]; Peng et al, 2020 [ 31 ]); ( B ) extracellular microvesicles (EMVs)—the exterior plasma membrane of activated microglia (AM) can release (R) 100–1000 nm diameter EMVs directly from the outward blebbing of the plasma membrane of microglias and astrocytes and carry intracellular contents from their cells of origin; this includes various complex mixtures of proteins, lipids, proteolipids, miRNAs, mRNAs, end-stage metabolic products and cytokines and chemokines; together these EMV contents may be pathogenic and cause the spread of pro-inflammatory signaling and inflammatory neurodegeneration (Prada et al, 2018 [ 21 ]; Serpente et al, 2020 [ 22 ]; Vanherle et al, 2020 [ 4 ]). Microvesicular trafficking and the extracellular microvesicle uptake (U) by neurons (N) via directed translocation mechanisms (dashed black lines with black arrowheads) may occur via the direct fusion of the EMV membrane with the neuronal cell plasma membrane or by endocytosis (Stahl et al, 2019 [ 5 ]; Arbo et al, 2020 [ 6 ]; Hornung et al, 2020 [ 30 ]; Peng et al, 2020 [ 32 ]; Song et al, 2020 [ 9 ]; Upadhya et al, 2020 [ 20 ]).…”
Section: Figurementioning
confidence: 99%
“… Highly schematized representation of ( A ) the release of exosomes (EXs) and ( B ) the release and uptake of extracellular microvesicles (EMVs) in neural cells of the human central nervous system (CNS); both types of vesicular transport systems have been observed to operate in the brain between astroglial cells and neurons; ( A ) exosomes—when mature intracellular endosomes (also known as multi-vesicular bodies) containing intraluminal vesicles (ILVs; black outlined green spheres) fuse with the plasma membrane and empty their plasma membrane-encapsulated cargo, ILVs are released and, from being extracellular, they become exosomes (EX); these 30–100 nm diameter spheres contain various mixtures of proteins, lipids, proteolipids, cytokines, chemokines, microRNAs (miRNA), messenger RNAs (mRNA) and end-stage neurotoxic metabolic products, including 42 amino acid amyloid-beta (Aβ42) peptides, tau proteins and/or the lipid raft associated flotillin (Angelopoulou et al 2020 [ 29 ]; Hornung et al, 2020 [ 30 ]); EXs appear to play a central role in the spread of Aβ42 pathology and amyloidogenesis (Mathews and Levy 2019 [ 15 ]; Arbo et al, 2020 [ 6 ]; Peng et al, 2020 [ 31 ]); ( B ) extracellular microvesicles (EMVs)—the exterior plasma membrane of activated microglia (AM) can release (R) 100–1000 nm diameter EMVs directly from the outward blebbing of the plasma membrane of microglias and astrocytes and carry intracellular contents from their cells of origin; this includes various complex mixtures of proteins, lipids, proteolipids, miRNAs, mRNAs, end-stage metabolic products and cytokines and chemokines; together these EMV contents may be pathogenic and cause the spread of pro-inflammatory signaling and inflammatory neurodegeneration (Prada et al, 2018 [ 21 ]; Serpente et al, 2020 [ 22 ]; Vanherle et al, 2020 [ 4 ]). Microvesicular trafficking and the extracellular microvesicle uptake (U) by neurons (N) via directed translocation mechanisms (dashed black lines with black arrowheads) may occur via the direct fusion of the EMV membrane with the neuronal cell plasma membrane or by endocytosis (Stahl et al, 2019 [ 5 ]; Arbo et al, 2020 [ 6 ]; Hornung et al, 2020 [ 30 ]; Peng et al, 2020 [ 32 ]; Song et al, 2020 [ 9 ]; Upadhya et al, 2020 [ 20 ]).…”
Section: Figurementioning
confidence: 99%
“…Recent evidence has pointed out a role of flotillin as a novel AD biomarker [ 79 , 80 ]. This is a membrane-associated protein located in lipid rafts of intra- and extracellular vesicles; therefore, it plays important roles in signal transduction and membrane–protein interactions.…”
Section: Emerging Ad Biomarkers In Biological Fluidsmentioning
confidence: 99%
“…This is a membrane-associated protein located in lipid rafts of intra- and extracellular vesicles; therefore, it plays important roles in signal transduction and membrane–protein interactions. Regarding AD pathogenesis, flotillin is involved in several pathological processes, such as APP processing and endocytosis, mitochondrial dysfunction, Aβ-induced neurotoxicity and neuronal apoptosis [ 80 ]. A clinical study reported that flotillin levels were decreased in both CSF and serum of AD patients compared with MCI individuals or age-matched non-AD controls.…”
Section: Emerging Ad Biomarkers In Biological Fluidsmentioning
confidence: 99%
“…However, the development of super-resolution microscopy permitted the observed lipid rafts in various cell types, leading to the wider acceptance of this concept (Owen et al, 2012 ). There are several styles of super-resolution microscopy that use distinct probes; each of these methods has successfully permitted the visualization of lipid rafts (Tobin et al, 2014 ; Chen et al, 2015 ; Hartley et al, 2015 ; Stahley et al, 2016 ; Gao et al, 2017 ; Schlegel et al, 2019 ; Angelopoulou et al, 2020 ). These new results have contributed to models suggesting possible roles for lipid rafts in multiple cellular pathways (Raghunathan and Kenworthy, 2018 ).…”
Section: Membrane Recycling Mechanisms In Lipid Rafts; Newly Observedmentioning
confidence: 99%